2019
DOI: 10.1002/adma.201901578
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Beam Epitaxy Scalable Growth of Wafer‐Scale Continuous Semiconducting Monolayer MoTe2 on Inert Amorphous Dielectrics

Abstract: Transition metal dichalcogenides (TMDs) (MX 2 , M = Mo or W, X = S, Se, or Te) have attracted intense interest for developing ultrascaled electronics and optoelectronics by virtue of their attractive 2D layered structures and unique physical properties that are absent in their bulk counterparts. [1][2][3][4][5] Monolayer semiconducting TMDs show sizable direct bandgaps, quantum confinement effects, large exciton binding energies and effective valley polarizations, which unveils widespread applications in field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 65 publications
0
40
0
Order By: Relevance
“…191,192 Hence, modifying the metalsemiconductor contact interface is an effective strategy to improve device performance. Specifically, using metallic 2D materials (graphene, 193 some 1 T phase TMDs 47,187,[194][195][196][197] ) as electrodes for (opto)electronics through epitaxy growth 35 or phase transition 198,199 will alleviate the pining effect. In addition, transferring the prefabricated metal electrodes can also avoid creating defects and strains, resulting in an atomically sharp and near perfect metal/2D semiconductor interface.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…191,192 Hence, modifying the metalsemiconductor contact interface is an effective strategy to improve device performance. Specifically, using metallic 2D materials (graphene, 193 some 1 T phase TMDs 47,187,[194][195][196][197] ) as electrodes for (opto)electronics through epitaxy growth 35 or phase transition 198,199 will alleviate the pining effect. In addition, transferring the prefabricated metal electrodes can also avoid creating defects and strains, resulting in an atomically sharp and near perfect metal/2D semiconductor interface.…”
Section: Discussionmentioning
confidence: 99%
“…2 Wafer-scale 2D materials prepared by various methods can be regarded as the atomically thin blocks for building large-scale vdWHs. Taking advantages of well controlling of preparation process on atomic scale, wafer-size 2D materials have been reported to be synthesized through diverse methods, including CVD, [37][38][39][40][41][42] pulsed laser deposition (PLD), 43,44 atomic layer deposition (ALD), 45,46 molecular beam epitaxy (MBE), 47,48 thermal evaporation, 49 controlled crack propagation, 50 Au-assisted mechanical exfoliation, 51 and solution processing. [52][53][54][55] In recent years, a mass of researches have been conducted to nondestructively transfer and integrate the fragile wafer-size 2D materials with as few contaminants as possible.…”
Section: Mechanical-assembly Stackmentioning
confidence: 99%
See 1 more Smart Citation
“…The mobilities determined from 100 devices fell in a narrow range of 19.2-27.0 cm 2 V -1 s -1 , comparable with exfoliated flakes, suggesting the relative high-quality uniformity. [134] Liu et al also reported to grow wafer-scale 8 nm 2D ferromagnetic Fe 3 GeTe 2 films on sapphire by MBE, with confirmation of a van der Waals gap of 0.82 nm by HR-TEM measurements and indication of high-crystalline quality by RHEED pattern. [171] This shows the versatility of the TMC material that MBE is able to grow.…”
Section: Physical Vapor Depositionmentioning
confidence: 93%
“…Among various 2DLMs already explored, transition metal dichalcogenides (TMDs) exhibit interesting electronic properties, especially tunable bandstructures which depend on the conditions including material composition, thickness and crystal phases [8][9][10][11][12]. TMDs have a general formula of MX 2 , where M and X represents a transition metal (e.g., Mo, W, Pt) and chalcogen (e.g., S, Se, Te), respectively, indicating versatile electronic properties by the combination of various elements (more than 30 TMDs) [13][14][15][16]. Moreover, the 2D nature of TMDs allows thickness controlled quantum confinement and vdWs stacking without lattice mismatch, which gives additional degree of freedoms on material engineering for electronic application [1,17,18].…”
Section: Introductionmentioning
confidence: 99%